Circulating tumor cells: A step toward precision medicine in hepatocellular carcinoma. Issue 7 (16th May 2022) - Teng, Pai‐Chi; Agopian, Vatche G; Lin, Ting‐Yi; You, Sungyong; Zhu, Yazhen; Tseng, Hsian‐Rong; Yang, Ju Dong
Abstract: Serum alpha‐fetoprotein and radiologic imaging are the most commonly used tests for early diagnosis and dynamic monitoring of treatment response in hepatocellular carcinoma (HCC). However, the accuracy of these tests is limited, and they may not reflect the underlying biology of the tumor. Thus, developing highly accurate novel HCC biomarkers reflecting tumor biology is a clinically unmet need. Circulating tumor cells (CTCs) have long been proposed as a noninvasive biomarker in clinical oncology. Most CTC assays utilize immunoaffinity‐based, size‐based, and/or enrichment‐free mechanisms followed by immunocytochemical staining to characterize CTCs. The prognostic value of HCC CTC enumeration has been extensively validated. Subsets of CTCs expressing mesenchymal markers are also reported to have clinical significance. In addition, researchers have been devoting their efforts to molecular characterizations of CTCs (e.g. genetics and transcriptomics) as molecular profiling can offer a more accurate readout and provide biological insights. As new molecular profiling techniques, such as digital polymerase chain reaction, are developed to detect minimal amounts of DNA/RNA, several research groups have established HCC CTC digital scoring systems to quantify clinically relevant gene panels. Given the versatility of CTCs to provide intact molecular and functional data that reflects the underlying tumor, CTCs have great potential as a noninvasive biomarker in HCC. Large‐scale, prospective studies for HCC CTCs with a standardized protocol are necessary for successful clinical translation.